Technical Efficiency in Chilean Agribusiness Industry: A Metafrontier Approach. Issue 3 (25th January 2017) - Lakner, Sebastian; Brenes‐Muñoz, Thelma; Brümmer, Bernhard
ABSTRACT: This study models the technical efficiency in the Chilean agribusiness industry between 2001 and 2007 by taking into consideration the structural differences between the different subsectors meat, fruit & vegetables, dairy, milling, and bakery. We analyze firm data from the Annual National Industrial Survey (ENIA) totaling 2, 940 observations using a stochastic frontier model combined with a metafrontier model. We observe dynamic developments in the subsectors meat, fruit & vegetables, and dairy, with a pronounced export‐orientation. We show that especially meat and fruit & vegetables firms have experienced positive technological change, whereas dairy firms are exhibiting a slight decrease in efficiency and technical change. The milling and bakery subsectors, which mainly produce for the domestic market, show a rather constant status in efficiency and technical change. The results confirm that an in‐depth analysis of subsectors is necessary to evaluate the competitiveness of the agribusiness industry in Chile. [EconLit citations: D24; Q13].